2017
DOI: 10.1002/aic.15960
|View full text |Cite
|
Sign up to set email alerts
|

Flow of viscoelastic surfactants through porous media

Abstract: We compare the flow behavior of viscoelastic surfactant (VES) solutions and Newtonian fluids through two different model porous media having similar permeability: (a) a 3D random packed bed and (b) a microchannel with a periodically spaced pillars. The former provides much larger flow resistance at the same apparent shear rate compared to the latter. The flow profile in the 3D packed bed cannot be observed since it is a closed system. However, visualization of the flow profile in the microchannel shows strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Recent work suggests a key role played by flow instabilities in enhancing fluid recovery. Indeed, microfluidic experiments have shown that unstable flow is often characterized by a dramatic increase in η app , as described in Section —leading to a concomitant increase in Ca . This idea has been directly verified using oil globules trapped in a microfluidic porous medium: injecting polymer solutions can increase the apparent Ca by nearly an order of magnitude, thereby increasing oil recovery ( Figure a,b) .…”
Section: Improved Fluid Recovery From Porous Mediamentioning
confidence: 69%
“…Recent work suggests a key role played by flow instabilities in enhancing fluid recovery. Indeed, microfluidic experiments have shown that unstable flow is often characterized by a dramatic increase in η app , as described in Section —leading to a concomitant increase in Ca . This idea has been directly verified using oil globules trapped in a microfluidic porous medium: injecting polymer solutions can increase the apparent Ca by nearly an order of magnitude, thereby increasing oil recovery ( Figure a,b) .…”
Section: Improved Fluid Recovery From Porous Mediamentioning
confidence: 69%
“…Non-Newtonian fluid sometimes exhibit time dependent velocity fluctuations in the flow fields which are reminiscent of turbulence, however they occur at very small Reynolds number, a phenomenon called elastic turbulence [24][25][26]. Elastic instabilities occur when the De number is sufficiently large, as reported experimentally for both polymeric [24,[27][28][29][30][31][32] and wormlike micellar solutions [33][34][35][36][37][38][39]. Numerical simulations also show the presence of such spatial and temporal elastic instabilities [26,[40][41][42].…”
Section: Introductionmentioning
confidence: 74%
“…The occurrence of such elastic instabilities in model porous media for HPAM was also shown in the work of Clarke et al [18], Kawale et al [60] and other researchers. Also for the VES solutions, recent studies of Zhao et al [61], Moss et al [55], and De et al [39] show that after a critical shear rate flow instabilities occur when flowing through a model porous medium. This elastic instability and excess flow resistance for VES is believed to be caused by the formation of transient shear induced structures [61].…”
Section: Relation Between Single and Multiphase Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal stresses due to shear should not be ignored as their contribution may be of the same magnitude as stresses due to extension [19]. De et al [22] numerically and experimentally studied the contribution of shear and extensional flows to the increased normal stresses of viscoelastic polymer solutions in a porous media, while Haward et al [14] investigated this contribution experimentally in a cross-slot device and they both found a large contribution of viscoelastic normal stresses in shear flow at high flow rates where elastic turbulence exists [23,24].…”
Section: Introductionmentioning
confidence: 99%